PENGGUNAAN ASAM LAKTAT SEBAGAI FEED ADITIF TERHADAP AKTIVITAS SGPT & SGOT AYAM SENTUL - Tri Rachmanto Prihambodo; Bambang Hartoyo; Efka Aris Rimbawanto (ANGON: Journal of Animal Science and Technology, 2022)
Background. The large number of species spread across Indonesia cannot be separated from the domestication process which helps improve and maintain livestock species by humans to maintain food needs for animals such as the domestication of the Sentul chicken. Poor feed efficiency for Sentul chickens has caused Sentul chickens to depend on antibiotics and has been banned since 2018. Lactic acid is believed to be an alternative to antibiotics and has been studied for a long time. The liver is an organ that can represent the state of the chicken if lactic acid is identified as a hazardous substance through the content of SGPT and SGOT. This study aims to evaluate the use of lactic acid as an acidifier in sentul chickens found in the liver seen from the content of SGOT and SGPT. Materials and Methods. There were 60 Sentul chickens used in this study which measured the content of SGOT and SGPT. Results. The addition of lactic acid significantly (p>0.05) did not have a negative effect on the liver in both SGOT and SGPT at administration levels up to 2% (v/g). SGOT and SGPT in the negative control were 232.9 and 39.68 mmol/L while the addition of lactic acid was still in a range that was not too far away, namely for SGOT in the range of 234.6-281.2 mmol/L and SGPT 35.15-56.96 mmol/L. Conclusion. The use of lactic acid in Sentul chicken feed does not cause liver damage which can be seen in SGOT and SGPT levels.